1991
DOI: 10.1530/jrf.0.0910187
|View full text |Cite
|
Sign up to set email alerts
|

Decreased follicular steroids and insulin-like growth factor-I and increased atresia in diabetic gilts during follicular growth stimulated with PMSG

Abstract: Four streptozotocin-diabetic gilts (maintained on exogenous insulin for 3 months) and 4 normoglycaemic gilts were treated with 600 i.u. PMSG. Diabetic gilts had insulin therapy removed at the time of PMSG administration. Plasma glucose averaged 463 +/- 5 mg/100 ml for diabetic gilts and 82 +/- 4 mg/100 ml for control gilts over the 72-h sampling period. Serum insulin was lower in diabetic than in normoglycaemic gilts (glycaemic state by time interaction; P less than 0.0001). At ovary removal 75 h after PMSG, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Insulin could support follicular development by reducing follicular atresia [23,24,43,44] and by suppressing follicular apoptosis [45]. Other in vivo studies also demonstrated that exogenous insulin treatment for 4 days in gonadotropintreated prepubertal gilts increased the number of follicles less than 3 mm in size [24], and maintained the 4-to 6-mm size follicle population in cyclic gilts when insulin treatment began on Day 15 of the cycle [23].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin could support follicular development by reducing follicular atresia [23,24,43,44] and by suppressing follicular apoptosis [45]. Other in vivo studies also demonstrated that exogenous insulin treatment for 4 days in gonadotropintreated prepubertal gilts increased the number of follicles less than 3 mm in size [24], and maintained the 4-to 6-mm size follicle population in cyclic gilts when insulin treatment began on Day 15 of the cycle [23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, LH has the ability to affect ovarian development directly (Cox and Britt, 1982;Rojanasthien et al, 1988;De Rensis et al, 1991). Local effects of insulin (Cox et al, 1987;Meurer et al, 1991) and nutrition (Flowers et al, 1988) on the number of follicles selected to ovulate have been established in gilts. However, the results of this experiment clearly indicate that the availability of additional nutrients during lactation did not increase ovulation rate or decrease the time to return to estrus.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma IGF-I concentrations and hepatic IGF-I gene expression have been shown to be affected by feeding level, it is not known whether fasting or feed restriction has the same effect on follicular fluid concentrations of IGF-I and on ovarian IGF-I gene expression in swine. There are, however, indications that decreased insulin levels may influence immunoreactive IGF-I levels within the ovaries of gilts and that this effect may be independent of gonadotrophins (Cox et al 1987;Meurer et al 1991). Cosgrove et al (1992) demon¬ strated that in chronically gonadotrophin-suppressed and feed-restricted gilts, refeeding was capable of stimulating ovarian development in the absence of an increase in gonadotrophin secretion.…”
Section: Introductionmentioning
confidence: 99%